Adsorption and Diffusion Characteristics of 2-Naphthol from Aqueous Media by Chitosan-ENR Biocomposites - R. GUNASUNDERI; M. R. H. MAS HARIS (ASEAN Journal on Science and Technology for Development, 2017)
Chitosan entrapped ENR-50 (CTS-t-ENR) biocomposites developed were studiedfor the absorption and desorption of 2-naphthol in aqueous media. Biocomposites comprising chitosan (CTS) immobilized or trapped in a partially crosslinked ENR (designated as CTS-t-ENR) was prepared by homogenising CTS in ENR-50 latex with curative agents in the presence of acetic acid. It was found that absorption increased with the increase in the initial 2-naphthol concentrations. Chitosan powder was found to be a poor absorbent compared CTS-t-ENR biocomposites. Desorption studyrevealed that the 2-naphthol diffusedslowly in water. The biocomposites exhibited a good slow-release properties and this was proven by the kinetic studyusing zero order, firsorder, Higuchi equation and Kosmeyer Peppas equation. Thus, these biocomposites with a good controlled release and swelling properties could be very useful in agricultural application.